The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1159/000138768
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Hyperreflexia: Effect of Intravesical Administration of Various Agents

Abstract: In anesthetized rabbits, we can induce a significant degree of spontaneous activity in the urinary bladder by placing a ligature around the proximal portion of the external urethra. Previous studies characterized the activity as primarily reflex in nature, since intravesical hexamethonium selectively inhibited the hyperreflexia. In this current study we determined the effect of intravesical administration of a variety of compounds to inhibit the induced hyperreflexia. The following agents were tested at concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…Their presence is increased in human tissue obtained from patients with unstable bladders [Kinder and Mundy, 1987] as well as from animal models of out£ow tract obstruction [Malmgren et al, 1989;Kato et al, 1990], and it has been proposed that they contribute to overactivity of the bladder in such patients. The contractions are insensitive to tetrodotoxin but are attenuated by raised extracellular Mg and L-type Ca 2þ channel antagonists [Levin et al, 1991; and, as shown in this study, low concentrations of Ni 2þ . It is presumed that their origin is myogenic and does not originate from increased motor nerve excitability or activity, as spontaneous Ca 2þ transients can be recorded in isolated cells that are also greatly inhibited by nicardipine (Wu and Fry, unpublished data).…”
Section: Nicl 2 and Spontaneous Contractionssupporting
confidence: 78%
“…Their presence is increased in human tissue obtained from patients with unstable bladders [Kinder and Mundy, 1987] as well as from animal models of out£ow tract obstruction [Malmgren et al, 1989;Kato et al, 1990], and it has been proposed that they contribute to overactivity of the bladder in such patients. The contractions are insensitive to tetrodotoxin but are attenuated by raised extracellular Mg and L-type Ca 2þ channel antagonists [Levin et al, 1991; and, as shown in this study, low concentrations of Ni 2þ . It is presumed that their origin is myogenic and does not originate from increased motor nerve excitability or activity, as spontaneous Ca 2þ transients can be recorded in isolated cells that are also greatly inhibited by nicardipine (Wu and Fry, unpublished data).…”
Section: Nicl 2 and Spontaneous Contractionssupporting
confidence: 78%
“…In previous studies using both isolated strips of detrusor, and an in vivo rabbit model of hyperreflexia, ZD6169 was a more potent inhibitor than cromakalim [5], These studies indicate that ZD 6169 may be clinically useful in the treatment of specific urinary bladder disorders characterized by hyperreflexia and/ or detrusor hyperactivity.…”
Section: Frequency (Hz)mentioning
confidence: 72%
“…Cromakalim abolishes spontaneous bladder contractions in pigs [5], rats [8] and rabbits [9] with bladder instability, with little change in other urodynamic variables. Cromakalim also lowers blood pressure in pigs when administered in doses that suppress the unstable contractions [5].…”
Section: Introductionmentioning
confidence: 95%